CHARACTERIZATION OF LASER MEDIUM BASED ON ZINC BARIUM BORO-TELLURITE GLASS DOPING WITH RARE-EARTH IONS (Sm3+, Eu3+, AND Dy3+) - SUAIF (NIM: 20216007), AHMAD
Laser is the optical device that broadly contributes in the development of fundamental sciences and engineering. Laser technology includes measurement, sensing, monitoring system, health, until industrial studies. Laser is grown with any characteristics to meet the standards of work in certain applications. In this study it is reported the manufacturing of laser medium based on Zinc Barium Boro-Tellurite (ZBBT) glass doped by rare-earth ions which is in lanthanide series such as Sm3+, Eu3+, and Dy3+. This study was conducted by inserting active ions into the glass matrix host by then observing the structural, physical, optical, luminescene, and lifetime properties of the medium. The chemical batch composition formulation of the glass matrix developed in this study of ZBBT glasses was (34-x) TeO2-30B2O3-30BaO-xZnO-[RE]O3 (x = 4; 9; 14; 19; and 24 mol%, with [RE] = Sm3+, Eu3+, and Dy3+). After a mixture of 15 grams of chemical substances stirred to form a homogeneous glass composition, subsequently it was conducted the melting of the sample using melt-quenching method by increasing the furnace temperature up to 1150 oC for 1 hour. Bonding structure of the samples reviewed with FTIR spectroscopy. Characterization of physical properties of the glass samples such as molecular weight, density, and molar volume has been conducted by densitometer along with theoretical calculation. The optical properties such as refractive index was using PRIM. A measurement of the luminescene and the lifetime properties was done by using spectrophotometer. Based on the measurement data of luminescene properties, it can be known some parameters such as absorption spectra, emission spectra, and the electron transition information.